Differentiated Learning Practices in Cognitive Development of Early Childhood: Praktik Pembelajaran Berdiferensiasi dalam Perkembangan Kognitif Anak Usia Dini - Novia Adeline Christie Ottay; Luluk Iffatur Rocmah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Early childhood education plays a critical role in establishing foundational cognitive abilities during the early developmental period. Specific Background Children aged 4–5 years require learning approaches that accommodate differences in readiness, interests, and learning styles to support cognitive growth. Knowledge Gap Although differentiated learning has been widely discussed in early childhood contexts, limited studies specifically describe its classroom implementation alongside supporting and inhibiting factors in early childhood institutions. Aims This study aims to describe the implementation of differentiated learning and identify supporting and inhibiting factors in developing cognitive development of children aged 4–5 years at TK Dharma Wanita Persatuan Tawangsari 2. Results Using a descriptive qualitative approach through observation, interviews, and documentation, the findings show that differentiated learning is implemented through curriculum-based planning, thematic play-based activities, and continuous developmental evaluation, with cognitive development supported by differentiated activities in literacy, numeracy, and arts. Supporting factors include teacher pedagogical competence, adaptive learning environments, parental support, and available learning facilities, while inhibiting factors involve limited infrastructure, diverse child backgrounds, and varying levels of parental involvement. Novelty This study provides a contextual description of differentiated learning practices integrated with density-based activities in early childhood classrooms. Implications The findings offer practical insights for early childhood educators and institutions in designing adaptive learning environments and strengthening collaboration between teachers, schools, and parents to support cognitive development in early childhood settings. Highlights: Differentiated activities were applied across literacy, numeracy, and arts based on children’s readiness levels. Teacher competence and adaptive classroom environments supported children’s cognitive growth. Infrastructure limitations and uneven parental involvement constrained classroom practices. Keywords: Early Childhood Education, Differentiated Learning, Supporting, Inhibiting Factors.